Why the poor pay higher energy prices: Evidence from Tanzania. (June 2022) - Olabisi, Michael; Richardson, Robert B.
Abstract: We show that poorer households pay higher per-unit prices for the most commonly-used cooking and lighting fuels, using rich, nationally-representative household-level data from Tanzania. The paper is motivated by the concern that poor households may be trapped in a cycle where they pay higher prices for necessities like cooking fuel, relative to others with higher income who pay lower prices for the same goods. Our analysis shows that for charcoal, the most commonly used cooking fuel in our data, much of the poverty penalty faced by poor households can be explained by their pattern of buying in small quantities. Higher-income households obtain lower prices by buying higher quantities per transaction, on average. The findings have policy implications for enhancing household energy security.